ENHANCING ENGLISH TEACHERS' PEDAGOGICAL COMPETENCE THROUGH LESSON STUDY ACTIVITIES - Margana Margana (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2011)
This article deals with the implementation of Lesson Study to enhance pedagogical competence of English teachers of senior high schools at Bantul Regency, Yogyakarta. It is aimed at describing the implementation of Lesson Study at 5 senior high schools. The Lesson Study was implemented in five cycles. There were 10 English teachers involved in the study. They engaged in three activities, namely Plan, Do, and See.Â In PLAN, the 10 English teachers under the lecturerâ€™s supervision did lesson planning. In DO, one of the English teachers acted out as a model teacher and the rest observed the teaching and learning process targeting learner activities as the angle of the observation practices. In SEE, the participants were engaged in reflecting the teaching learning process. Two techniques: observation and interview were utilized to obtain data from the participants. The result of the study shows that 10 English teachers involved in the study got direct pedagogical competence through the implementation of Lesson Study. Added to this, they claim that the Lesson Study activities provide them with lesson planning skills and teaching skills and encourage them to be self-confident in conducting the English teaching and learning process Key words: English Teacher, Lesson Study, Pedagogical Competence